Assessment of Hospital Emergency Response Against Disasters Hospitals Of Iran University of Medical Siences: 2017 - Seyed Hesam Seyedin; Edris Hasanpoor; Ebrahim Hasanzadeh; Mohammadreza Sheikhy-Chaman (Kerman University of Medical Sciences, 2018)
Assessment of Emergency Response of Teaching Hospitals Affiliated to Iran University of Medical Silences against Disasters   Seyedin Seyed Hesam1, Hasanpoor Edris2, Hasanzadeh Ebrahim3, Sheikhy-Chaman Mohammadreza4*   1. Associate Professor, Student Research Committee, Department of Health Services Management, Iran University of Medical Sciences, Tehran, Iran 2. Assistant Professor, Department of Healthcare Management, Maragheh University of Medical Sciences, Maragheh, Iran 3. MSc Student, Student Research Committee, Department of Health Services Management, Iran University of Medical Sciences, Tehran, Iran 4. MSc Student, Department of Management Science and Health Economics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran *Correspondence: Department of Management Science and Health Economics, School of Public Health, Tehran University of Medical Sciences Tel: 00982188989129                                               Email: sheikhy-m@razi.tums.ac.ir   Abstract: Background & Objectives: In case of disasters, hospitals as one of the first centers to admit casualties, need to be well prepared. Emergency response of hospitals to deal with disasters is essential to success in providing qualified emergency services. The aim of this study was to evaluate emergency response of teaching hospitals affiliated to Iran University of Medical Sciences against disasters. Methods: This cross-sectional descriptive study was conducted in 14 teaching hospitals affiliated to Iran University of Medical Sciences in 2017. To collect data, hospital emergency response checklist provided by WHO (2011) with 90 questions in 9 domains (command and control, communication, safety and security, triage, surge capacity, continuity of essential services, human resources, logistics and supply management, and post-disaster recovery), was used. Data were analyzed using descriptive tests by SPSS version 15. Results: Mean score of emergency response of the hospitals against disasters was 56.93. The highest and lowest levels of response were related to human resources (63.57) and Materials and inventory management (57.03), respectively. Conclusion: Planning and providing a systematic framework to deal with disasters is essential, and the major role of hospitals in providing services should not be ignored, it should be considered as a priority in planning and budgeting for disasters.   Keywords: Emergency response, Hospital, Disasters, Iran University of Medical Sciences   Citation: Seyedin SH, Hasanpoor E, Hasanzadeh E, Sheikhy-Chaman MR. Assessment of Emergency Response of Teaching Hospitals Affiliated to Iran University of Medical Silences against Disasters. Journal of Health Based Research 2018; 4(2): 159-67. [In Persian]